2022
DOI: 10.5271/sjweh.4037
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and SARS-CoV-2 infection risk among 108 960 workers during the first pandemic wave in Germany

Abstract: This study provides first evidence for occupational differences in the risk of SARS-CoV-2 infection for Germany during the beginning of the pandemic. Findings confirm previous studies from Norway and the UK, reporting high infection rates in essential occupations and in personal services. In addition, we also test for vertical differences and find that infections were more common in higher occupational status positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
2
31
0
5
Order By: Relevance
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 59%
“…Data from Germany 12 (February – September 2020) and Sweden 13 (January 2020 – February 2021) indicates elevated risk of infection amongst essential workers – including health, care, and service workers – compared to non-essential workers across the respective study periods, after adjustment for a range of socio-demographic factors. However, occupational differences in risk may vary by global region and comparative investigation for the UK is limited.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 disease in the workplace will be a consequence of exposure to SARS-CoV-2 virus; workplace factors known to be related to exposure include ventilation, ability to social distance and number of daily contacts. 3 4 Several studies have found increased risks of infection and mortality from COVID-19 among healthcare workers [5][6][7][8] when compared with other workers. Other studies have not found an increased risk 9 or suggest it varies by type of worker and/or stage of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The evidence for whether this perceived exposure translates to increased infection and/or mortality is varied. 8 10 15 16 18–21 This can be partially explained by different approaches to ascertaining outcome, often using testing regimens linked to self-referral or occupation. In addition, different time periods had different mitigation strategies in place.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, research into risks of COVID-19 by occupation would be based on cases ascertained through systematic prospective follow-up of large cohorts of workers, with regular ascertainment of symptoms, clinical signs, and polymerase chain reaction (PCR) testing. As that has not been feasible, researchers have been forced to use proxy measures of incidence based on: PCR testing (4)(5)(6)(7)(8)(9)(10)(11), measurements of specific immunoglobulins against SARS-CoV-2 (12)(13)(14), symptoms and sickness absence (6), COVID-19 related hospital admission (7,15,16), or mortality from the disease (7,15,(17)(18)(19)(20)(21)(22). In most studies to date, with broad coverage of occupations, mortality from COVID-19 has been the outcome measure (7,15,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%